Osteosynthesis of a cranio-osteoplasty with a biodegradable magnesium plate system in miniature pigs. (15th October 2017) - Naujokat, Hendrik; Seitz, Jan-Marten; Açil, Yahya; Damm, Timo; Möller, Inga; Gülses, Aydin; Wiltfang, Jörg
Graphical abstract: Abstract: Biodegradable magnesium alloys are a new class of implant material suitable for bone surgery. The aim of this study was to investigate plates and screws made of magnesium for osteosynthesis in comparison to titanium in a cranial fracture model. Implants were used for internal fixation of a cranio-osteoplasty in nine minipigs. Computed tomography was conducted repeatedly after surgery. The implants and the adjacent tissues were harvested 10, 20 and 30 weeks after surgery and investigated by micro-computed tomography and histological analysis. The surgical procedure and the inserted osteosynthesis material were well tolerated by the animals, and the bone healing of the osteoplasty was undisturbed at all times. The adjacent bone showed formation of lacunas in the magnesium group, resulting in a lower bone-to-implant contact ratio than that of titanium (72 vs. 94% at week 30), but this did not lead to clinical side effects. Radiological measurements showed no reduction in osteosynthesis material volume, but indicated signs of degradation: distinct volumes within the magnesium osteosynthesis group had lower density in micro-computed tomography, and these volumes increased up to 9% at week 30. The histological preparations showed areas of translucency and porosity inside the magnesium, but the outer shape of the osteosynthesis material remained unchanged. No fracture or loosening of the osteosynthesis devices appeared. Soft tissue probes confirmed sufficient biocompatibility. Given their biodegradable capacity, biocompatibility, mechanical strength and visibility on radiographs, osteosynthesis plates made of magnesium alloys are suitable for internal fixation procedures. Statement of Significance: To the best of our knowledge this is the first study that used biodegradable magnesium implants for osteosynthesis in a cranial fracture model. The cranio-osteoplasty in miniature pigs allowed in vivo application of plate and screw osteosynthesis of standard-sized implants and the implementation of surgical procedures similar to those conducted on human beings. The osteosynthesis configuration, size, and mechanical properties of the magnesium implants within this study were comparable to those of titanium-based osteosynthesis materials. The results clearly show that bone healing was undisturbed in all cases and that the biocompatibility to hard- and soft tissue was sufficient. Magnesium implants might help to avoid long-term complications and secondary removal procedures due to their biodegradable properties.